2017
DOI: 10.1177/0885066617732284
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Matrix Metalloproteinases and Their Inhibitors for Mortality in Septic Patients: A Cohort Study

Abstract: Although TIMP-1 showed higher sensitivity, specificity, and negative predictive value, with a representative population sample, we conclude that none of the evaluated biomarkers had significant predictive value for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 41 publications
5
12
2
1
Order By: Relevance
“…Previous studies also demonstrated lower MMP-9 [ 8 , 9 , 15 ] and higher TIMP-1 [ 8 , 12 , 13 , 15 ] in nonsurvivors and in patients with higher disease severity scores [ 6 , 12 ]. Lorente et al [ 8 ] and Wang et al [ 13 ], as opposed to Martin et al [ 9 ] and Serrano-Gomez et al [ 14 ], supported our findings that MMP-9, TIMP-1, and MMP-9/TIMP-1 ratio are good prognostic biomarkers of 28-day survival. A recent study by Niño et al, however, demonstrated that only TIMP-1 and not MMP-9 and MMP-9/TIMP-1 ratio was a good predictor of mortality in sepsis [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies also demonstrated lower MMP-9 [ 8 , 9 , 15 ] and higher TIMP-1 [ 8 , 12 , 13 , 15 ] in nonsurvivors and in patients with higher disease severity scores [ 6 , 12 ]. Lorente et al [ 8 ] and Wang et al [ 13 ], as opposed to Martin et al [ 9 ] and Serrano-Gomez et al [ 14 ], supported our findings that MMP-9, TIMP-1, and MMP-9/TIMP-1 ratio are good prognostic biomarkers of 28-day survival. A recent study by Niño et al, however, demonstrated that only TIMP-1 and not MMP-9 and MMP-9/TIMP-1 ratio was a good predictor of mortality in sepsis [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…Analogous findings were reported for sepsis-associated organ dysfunction after major abdominal surgery by another study group [51]. Taking into account positive and negative predictive values, however, Serrano-Gomez et al found neither MMP-9, MMP-2, TIMP-1, TIMP-2 nor their respective ratios to have significant predictive values in mortality of sepsis patients [52]. The TIMP-1 has been associated with survival in several other critical diseases, including traumatic brain injury [53,54], cerebral infarction [55], graft versus host disease [56] and acute respiratory failure [57].…”
Section: Discussionsupporting
confidence: 62%
“…Thus, it is plausible to assume that MMPs and TIMPs in previous studies have been determined at a time-point when the patients have been more severely ill. This is probably the major explanation for the much higher mortality rates reported in previous studies: 13–34% overall sepsis or ICU mortality [ 25 , 29 ] and 12–33% 30-days mortality or 27% 90-day mortality in septic and/or critically ill patients [ 13 15 , 25 34 ] as compared to 13% and 18% mortality rates at 28 and 90 days in the present study.…”
Section: Discussionsupporting
confidence: 45%
“…No corresponding trend at was seen for TIMP-1. Previous reports have observed higher MMP-8 on [ 25 ] and TIMP-1 [ 13 , 23 , 25 , 29 ] at sepsis onset or ICU admission in non-surviving sepsis patients compared to surviving ones. Furthermore, two reports observed that critically ill non-surviving patients at ICU admission or in need of mechanical ventilation, as compared to surviving ones, presented higher MMP-8 and TIMP-1 levels [ 14 , 15 ] but indifferent MMP-8/TIMP-1 molar ratios [ 15 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation